Influence of Moral Education, Organizational Involvement, and Social Participation on Environmental Awareness Attitudes - Azwar, Wahyu Azwar; Syaharuddin, Syaharuddin; Isnaini, Isnaini; Hafsah (LPPM STKIP Kusuma Negara, 2025)
The lack of awareness and environmental care among university students is a critical issue that requires attention. This study aims to investigate the influence of moral education, organizational involvement, and social participation on environmental concern among students in the Faculty of Education and Teacher Training. The research employed a quantitative method with a survey approach, involving 67 participants. The research instrument utilized a Likert scale with 31 questions. The results of the multiple regression analysis revealed that moral education, organizational involvement, and social participation significantly affect students' environmental concern. The regression value of 70.4% indicates a high level of model explanation. Anova F yielded a value of 49.873, demonstrating the overall significance of the model, while the sig value < 0.05 is 0.001 confirms the significance of each independent variable. This study makes a substantial contribution to understanding the factors influencing environmental concern among Faculty of Education and Teacher Training student. This research confirms that moral education integrated with organizational activities and social participation can be an effective strategy to increase students' environmental awareness. So, it is expected that there will be environmental character-based curriculum development, as well as active involvement of students in sustainability-based social activities.